Funding Liquidity and Risk-Taking: Evidence from the Commercial Banks of Pakistan - Sidra Gazali; Asma Zeeshan; Shahab Aziz; Muhammad Kamran Khan (International Journal of Business and Economic Affairs, 2023)
This study aims to examine the impact of funding liquidity risk on banks’ risk appetite using annual data from 23 commercial banks listed on the Pakistan Stock Exchange for the period of 10 years, i.e., from 2011-2020. The study finds that banks with lower liquidity risk (as measured by the ratio of deposits to total assets) take on higher risk. The result showed that increasing deposition leads to an increase in Loan Loss Provision (LLP), -Z-score, and standard deviation of bank stock returns (SRV). However, the result showed that bank size and the capital buffer have a significant impact on banks’ risk appetite in the event of excessive deposits. The outcome of the study has practical implications for banking regulators to encourage higher liquidity and capital requirements for banks. Thus would increase customers confidence in commercial banks by reducing danger of bank run and disciplining risk taking behavior of banks.